Hybridization as a biodiversity driver: The case of Veronica × gundisalvi - López-González, Noemí; Bobo-Pinilla, Javier; Gutiérrez-Larruscain, David; Martínez-Ortega, Maria Montserrat; Rojas-Andrés, Blanca María (Mediterranean Botany, 2021)
Hybridization is an important mechanism in plant evolution, which contributes to the adaptability and biological diversity of species in fundamental ways. Based on morphological data, Veronica × gundisalvi Sennen (Veronica orsiniana × V. tenuifolia subsp. tenuifolia) is an Iberian endemic taxon of presumably polytopic hybrid origin restricted to five localities in Catalonia, where the putative parental species grow in sympatry. In this study, species distribution models were developed for the putative parental species to seek potential new localities where active hybridization could be taking place. As a result, a new location of this nothotaxon in Zaragoza is provided, along with a chromosome count and ploidy level estimations. The data presented here further support Veronica × gundisalvi as a homoploid hybrid taxon that occurs in non-altered habitats. In contrast to the traditional view of hybridization as deleterious for the conservation of biodiversity, it does not always represent a problem in this regard. Hybridization is a complex evolutionary force that requires case-specific evaluation. Given that biodiversity loss is one of the main contemporary challenges, it is important to consider the creative nature of hybridization, a widespread evolutionary mechanism able to produce novel diversity.